Structural parameters governing activity of Pluronic triblock copolymers in hyperthermia cancer therapy - KRUPKA, TIANYI M. (2011)
PURPOSE: To identify specific Pluronic triblock copolymer structural properties which are critical to its function as a sensitiser in hyperthermia treatment of experimental colorectal adenocarcinoma. MATERIALS AND METHODS: DHD/K12/TRb rat colorectal adenocarcinoma cells were exposed to Pluronics, a family of triblock copolymers with the general structure EO(x)-PO(y)-EO(x) (EO: ethylene oxide, and PO: propylene oxide), at a range of molecular weights (Mw) and EO:PO:EO sub-unit lengths and then submitted to sublethal heat (43°C) treatment. Outcomes indicating Pluronic performance as a thermal sensitiser were correlated with its structural properties; lead candidates were determined accordingly. Finally, one of the lead candidates, Pluronic L61, a 2000 Da copolymer, was used to assess sensitising functionality in vivo in a subcutaneous rat model of colorectal carcinoma. RESULTS: Pluronics with 1100 ≤ Mw ≤ 3200 Da and hydrophilic lipophilic balance (HLB) between 1–8 demonstrated the highest thermosensitising ability. Pluronics L31, L61, L62, L10 and L64 were found to be among the most effective copolymers for hyperthermia sensitisation under tested conditions. Most encouraging, L61 in synergy with hyperthermia significantly reduced tumour growth progression in vivo compared to tumours treated with hyperthermia alone. CONCLUSIONS: Pluronic copolymer structure properties including, Mw, HLB and PO length are essential to its hyperthermia sensitising function.